1986
DOI: 10.1099/0022-1317-67-7-1283
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Structure of Polioviruses of Serotypes 1, 2 and 3

Abstract: SUMMARYThe antigenic sites recognized by monoclonal antibodies with neutralizing activity for the Sabin vaccine strains of poliovirus of serotypes 1, 2 and 3 have been studied by the isolation and characterization of mutants resistant to neutralization by antibody. Three distinct sites have been identified which are designated site 1, site 2 and site 3. Site 1 includes a region of 12 amino acids of VP1, from residues 89 to 100, and a corresponding region of VP1 has been identified as an antigenic site for poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
234
1
3

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 296 publications
(249 citation statements)
references
References 20 publications
11
234
1
3
Order By: Relevance
“…The constructs made are shown in Table 1. Viruses were recovered by transfection of Hep2c cells (Burke et al, 1988) and the sequence of the insert was checked by sequencing the genomic RNA (Minor et al, 1986). All viruses were neutralized by pooled human serum and infection was prevented by an MAb specific for the poliovirus receptor (Minor et al,199O).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The constructs made are shown in Table 1. Viruses were recovered by transfection of Hep2c cells (Burke et al, 1988) and the sequence of the insert was checked by sequencing the genomic RNA (Minor et al, 1986). All viruses were neutralized by pooled human serum and infection was prevented by an MAb specific for the poliovirus receptor (Minor et al,199O).…”
Section: Methodsmentioning
confidence: 99%
“…The antigenic structure of poliovirus has been studied extensively, and several sites to which neutralizing antibodies bind have been identified by the isolation and characterization of antigenic variants (Minor et al, 1983(Minor et al, , 1986Diamond et al, 1985;Blondel et al, 1986;Page et al, 1988;Wiegers et al, 1989). The atomic structures of the type 1 strain Mahoney (Hogle et al, 1985) and the Sabin type 3 strain Leon 12alb (Filman et al, 1989) have been determined, and the antigenic sites have been shown to form apparently distinct structural features on the virus surface.…”
Section: Introductionmentioning
confidence: 99%
“…PV2-32191 had two substitutions in the capsid coding region. The first was in VP3, at the recognized neutralizing antigenic site 3B (Minor et al, 1986a), and the second in VP1-143, in the known attenuation site exposed in the DE-loop (Hogle et al, 1985). The amino acid substitution in PV2-32189+AP1, in addition to the VP1-143 substitution, resided in the nonstructural protein coding region in 2A, with no known specific biological function.…”
Section: Genetic Featuresmentioning
confidence: 99%
“…Direct analysis using monoclonal antibody escape mutants showed that some of these regions corresponded to neutralizing antigenic sites and this has allowed the production of synthetic peptides as potential vaccines and for probing the antigenic structure (Minor et al, , 1986aFerguson et al, 1985;DiMarchi et al, 1986;Sherry et al, 1986). Alignment of sequences also enables the corresponding antigenic regions in viruses not studied directly to be identified.…”
Section: Capsid Proteinsmentioning
confidence: 99%